1995
DOI: 10.2172/105886
|View full text |Cite
|
Sign up to set email alerts
|

Organic tank safety project: Preliminary results of energetics and thermal behavior studies of model organic nitrate and/or nitrite mixtures and a simulated organic waste

Abstract: Appendix A -Thermal Behavior of and Evolved.Gases from 2 and 10 Mass% TOC Mixtures of Acetate, Citrate, EDTA, and HEDTA and Equimolar Sodium Nitrate and Nitrite as Measured by DSC, TGA, ARC, and IR . . . .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 21 publications
(51 reference statements)
6
34
0
Order By: Relevance
“…It is shown that the amount of heat produced or o6served by the two instruments is a fraction of the maximum theoretical enthalpy. One possible explanation is that the reaction between the organics and the nitrate proceed, at least partially, by a less energetic reaction pathway than predicted by theory, which is consistent with previously obtained results (Scheele et al 1995).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…It is shown that the amount of heat produced or o6served by the two instruments is a fraction of the maximum theoretical enthalpy. One possible explanation is that the reaction between the organics and the nitrate proceed, at least partially, by a less energetic reaction pathway than predicted by theory, which is consistent with previously obtained results (Scheele et al 1995).…”
supporting
confidence: 90%
“…For example, it has been shown that ammonia is among the gases released during decomposition .of organics such as sodium acetate and sodium HEDTA. (Scheele et al 1995). This is direct evidence of different dissociation reaction pathways being followed by many of these organics of interest than predicted by calculated reaction enthalpies, where primarily nitrogen and nitrous oxide gases are expected (Burger 1995).…”
Section: Measured Energetics For Equimolar Sodium Nitrate and Nitritementioning
confidence: 76%
“…The reaction observed with a maximum cooling rate near 150°C may correspond to the endothermic reaction observed by Scheele et al (1995) for a mixture of sodium nitrate and nitrite. The change in slope for the pressure results observed beginning between 140 and 150'C suggests that gas is released during this endothermic reaction.…”
Section: Thermal Reactivity Of Mixtures Of Polywater@ Residue and 101supporting
confidence: 58%
“…This is based on the DSC-, TGA-, and ARC-observed behavior of the NqHEDTA and equimolar sodium nitrate and nitrite mixture presented in Figure 5.2 (Scheele et al 1995) During the ARC analysis, the absence of significant pressure increases that would be predicted based on Bryan's TGA (Figure 5.3) is likely due to differences in the drying method between our lOlSY/HEDTA and Bryan's preparation. SA Bryan dried his lOISY/HEDTA at 50'C under a vacuum for 2 to 3 days compared to our 2 to 3 weeks; Bryan did not dry the simulant to a stable (a) Provided by the courtesy of SA Bryan of PNNL and the PNNL Flammable Gas Project.…”
Section: Thermal Reactivity Of 101syihedtamentioning
confidence: 79%
See 1 more Smart Citation